The effect of student-led healthcare career experience activity on nursing students’ professional commitment: Study protocol for a randomized cross-over trial - Shilai Yang; Yanli Lv; Biaojun Yu; Weiling Chen; Jin Peng; Mohd Afifuddin Mohamad (PLoS ONE, 2026)
Background Career experience is a valuable approach to stimulate students’ learning interest and reshape their understanding of career pathways. However, the interaction effects between implementers and experiencers, particularly the benefits of the implementers, remain poorly understood. Furthermore, the role of peer-assisted learning in enhancing the effectiveness of career experience activities has not been thoroughly explored. This study aims to evaluate the impact of student-led healthcare career experience activity on nursing students’ professional commitment, academic self-efficacy and learning burnout. Methods This is the study protocol for an open-label, randomized stepped-wedge crossover trial. This study will be set in a medical vocational college in China and will include 110 nursing students, who will be randomly allocated (1:1:1) to one of three groups. In a sequential, stepped-wedge manner, the groups will cross over from control conditions (Waitlist and Observer) to the intervention, where they will lead a healthcare career experience activity. The primary outcome of professional commitment, as well as the secondary outcomes of academic self-efficacy and learning burnout, will be measured via self-reported questionnaires at baseline and three subsequent time points (after the 4th, 8th, and 12th activity sessions). Data will be analyzed using Generalized Estimating Equation (GEE) analysis. Conclusion This protocol details a student-led healthcare career experience activity, grounded in Kolb’s Experiential Learning Theory and Life Cycle Theory, and designed to enhance nursing students’ professional commitment. This trial is expected to provide empirical evidence on the feasibility of this peer-assisted learning model applied in a student-led nursing educational scenario, which facilitates both peer-to-peer and near-peer interactions. Furthermore, the outcomes are expected to inform the future development of student-led educational strategies. Trial registration This study is registered in Chinese Clinical Trial Registry (ChiCTR2300070880). https://www.chictr.org.cn/bin/project/edit?pid=195337